2011
DOI: 10.19173/irrodl.v12i3.873
|View full text |Cite
|
Sign up to set email alerts
|

Interconnecting networks of practice for professional learning

Abstract: The article explores the complementary connections between communities of practice and the ways in which individuals orchestrate their engagement with others to further their professional learning. It does so by reporting on part of a research project conducted in New Zealand on teachers' online professional learning in a university graduate diploma program on ICT education. Evolving from social constructivist pedagogy for online professional development, the research describes how teachers create their own ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 28 publications
0
33
0
1
Order By: Relevance
“…Novice teachers engaged in collaboration and reflection with PLNs and receiving feedback from veteran teachers, who are also engaged with the same PLNs, benefit through the application of praxis and world knowledge afforded through this collaboration and reflection (Beach 2012;Craig & Stevens, 2011;Kabilan et al, 2011;King, 2011;Mackey & Evans, 2011;Reich et al, 2011;Trust 2012). Twitter supports teachers' PLNs by creating and facilitating interactions among the educators involved in connected, collaborative, and interactive meaning making.…”
Section: Professional Learning Network and Professional Growth Throumentioning
confidence: 99%
See 2 more Smart Citations
“…Novice teachers engaged in collaboration and reflection with PLNs and receiving feedback from veteran teachers, who are also engaged with the same PLNs, benefit through the application of praxis and world knowledge afforded through this collaboration and reflection (Beach 2012;Craig & Stevens, 2011;Kabilan et al, 2011;King, 2011;Mackey & Evans, 2011;Reich et al, 2011;Trust 2012). Twitter supports teachers' PLNs by creating and facilitating interactions among the educators involved in connected, collaborative, and interactive meaning making.…”
Section: Professional Learning Network and Professional Growth Throumentioning
confidence: 99%
“…Connectivism, a learning theory based on the premise that learning and knowledge rest in the diversity of opinions through the formation of connections, has emerged to explain how learning is interwoven with the creation of meaning by the sharing of social and historical practices, forming identity, and belonging to a community (Killion, 2011;Mackey & Evans, 2011;Siemens, 2005). In a network-based learning theory, individuals share knowledge with organizations and institutions, the nodes of the network responsible for learning exchange, which then delivers knowledge back to the individual, fostering continued learning (Siemens, 2005).…”
Section: Connectivism Networking and Community Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Many function in very small schools and are isolated from other teachers and education professionals, limiting their ability to physically collaborate and share with a larger group. The establishment of a PLN as an explicit byproduct of the OOC could help these teachers to create relationships which would assist them in ongoing professional development despite their often remote rural settings (Mackey & Evans, 2011;Tuck, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A study by Marrero, Woodruff, Schuster, and Riccio (2010) indicated that teachers who participated in online courses and learnt together with peers found this form of learning more supportive than traditional professional development workshops. Online professional development may provide opportunities for integrating teachers' experiences as learners and teachers, claim Mackey and Evans (2011).…”
Section: Introductionmentioning
confidence: 99%